Artificial Organelles for Energy Regeneration. Issue 6 (10th March 2019) - Otrin, Lado; Kleineberg, Christin; Caire da Silva, Lucas; Landfester, Katharina; Ivanov, Ivan; Wang, Minhui; Bednarz, Claudia; Sundmacher, Kai; Vidaković‐Koch, Tanja
Abstract: One of the critical steps in sustaining life‐mimicking processes in synthetic cells is energy, i.e., adenosine triphosphate (ATP) regeneration. Previous studies have shown that the simple addition of ATP or ATP regeneration systems, which do not regenerate ATP directly from ADP and Pi, have no or only limited success due to accumulation of ATP hydrolysis products. In general, ATP regeneration can be achieved by converting light or chemical energy into ATP, which may also involve redox transformations of cofactors. The present contribution provides an overview of the existing ATP regeneration strategies and the related nicotinamide adenine dinucleotide (NAD + ) redox cycling, with a focus on compartmentalized systems. Special attention is being paid to those approaches where so‐called artificial organelles are developed. They comprise a semipermeable membrane functionalized by biological or man‐made components and employ external energy in the form of light or nutrients in order to generate a transmembrane proton gradient, which is further utilized for ATP synthesis. Abstract : Adenosine triphosphate (ATP) is a crucial source of energy driving biological as well as biomimetic processes. In this work, light‐driven ATP regeneration systems and chemically driven ones, based on oxidative phosphorylation, are reviewed in the context of bottom‐up synthetic biology. Furthermore, nicotinamide adenine dinucleotide regeneration is discussed in the context of enhanced and sustainable ATP regeneration.